Paradigma dan Tantangan Pendidikan Seni dalam Mengintegrasikan Akhlaq, Teknologi, dan Multikulturalisme - Handayani, Lucy; Hartono; Saearani, Muhammad Fazli Taib Bin (Besaung : Jurnal Seni Desain dan Budaya, 2024)
Art education faces various paradigms and challenges in the modern era, where the integration of moral values, technological development, and multiculturalism is increasingly important. This study aims to examine the challenges and opportunities in integrating moral values, technology, and multiculturalism into art education. This research uses Creswell's naturalistic qualitative method. The results of this study include: First, moral values encompassing ethics, morality, and character are outlined as fundamental foundations in shaping students' personalities. Second, rapid technological development provides both opportunities and challenges in adapting innovative and interactive art learning methods. Third, multiculturalism and cultural diversity are important elements in enriching artistic perspectives and promoting inclusivity. Through this approach, it is hoped that art education can produce creative, critical, and character-driven individuals who are ready to face the ever-changing global dynamics.